A New Iterative Algorithm for Solving a Class of Matrix Nearness Problem. (8th December 2011) - Duan, Xuefeng; Li, Chunmei
Abstract : Based on the alternating projection algorithm, which was proposed by Von Neumann to treat the problem of finding the projection of a given point onto the intersection of two closed subspaces, we propose a new iterative algorithm to solve the matrix nearness problem associated with the matrix equations A X B = E, C X D = F, which arises frequently in experimental design. If we choose the initial iterative matrix X 0 = 0, the least Frobenius norm solution of these matrix equations is obtained. Numerical examples show that the new algorithm is feasible and effective.